Association of Helicobacter Pylori Infection and Stomach Cancer - Thapa, Narayan; Shah, Kunda Bikram; Bhandari, Bharat Bahadur; Hamal, Bhairab Kumar; Shrestha, Amar; Adhikari, Subodh Kumar (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Helicobacter pylori (H. Pylori) as a primary etiological factor in carcinoma stomach. Associationof H. Pylori in gastric cancer has been documented to be in more than 50% of cases. In underdevelopedcountries, this association is shown to be much higher according to different studies. Methods: A prospective observational study of 40 consecutive cases of carcinoma stomach was under takenin surgical department of Shree Birendra hospital and Bir hospital, for a period of two years 2009 to 2011.Location and pathological types of the lesion were noted and all specimens were investigated to see presenceof helicobacter pylori by rapid urease test (RUT) and histological examination. Results: Out of 40 patients, helicobacter pylori positivity was seen in 27 (67.5%) cases by both rapid ureasetest and Histopathological examination (HPE). Regarding the pathological types, out of 26 intestinal type of castomach, 20 (76.92%) cases were positive for H. pylori infection, whereas out of 14 diffuse type of ca stomach,7(50%) cases were positive for H. pylori. In 29 cases of distal ca stomach, H. pylori positivity was seen in 22(75.86%) cases, whereas in rest of the 11 cases the lesion involved other part of the stomach, H. pylori positivitywas seen in 5(45.45%) cases. Conclusion: Helicobacter pylori infection is higher in prevalence in cases of stomach cancer. Its associationwith intestinal histological type of stomach cancer is more common than diffuse type. There is higher prevalenceof Helicobacter pylori infection in distal carcinoma. doi: http://dx.doi.org/10.3126/mjsbh.v12i2.12927